Identification of genomic loci governing pericarp colour through GWAS in rice (Oryza sativa L.) - Sonah, Humira; Rana, Nitika; Kumawat, Surbhi; Singh, Uma Maheshwar; Singh, Vikas Kumar; Deshmukh, Rupesh; Sharma, Tilak Raj (Indian Society of Genetics and Plant Breeding, 2022)
Rice pericarp colour is one of the nutritional traits that is now gaining attention worldwide. In the present investigation, genome-wide association GWAS) was performed to identify loci governing pericarp colour in rice. A set of 1,349,269 SNPs and precise phenotyping across 325 diverse accessions of rice were used for the GWAS. The accessions belong to five rice isozyme classification groups viz., indica, japonica, aromatic, aus, and admix. The GWAS identified two significant loci gPC5-1and gPC7-1 on chromosomes, 5 and 7, respectively, associated with the pericarp colour in rice. The SNPs on chromosome 7 co-localized with the functionally characterized Os07g0211500 (Rc gene) known to control pericarp colour and Os07g0214900 which is similar to the Chalcone synthase 2(OsCHS2) gene involved in flavonoid synthesis pathway. Linkage disequilibrium analysis across 0.25 Mbp upstream and downstream of these markers suggested three strong linkage blocks on chromosome 7. More interestingly, the novel locus identified on chromosome 5 gPC5-1 does not harbor any homolog of previously reported genes. Therefore, the locus can serve as a basis for identifying a new gene for rice pericarp colour. The results presented here will be helpful to understand the genetic regulation of pericarp colour and for genomic-assisted breeding in rice.